POTENSI MASYARAKAT DALAM MENGURANGI PERMASALAHAN SAMPAH KOTA (Studi kasus di Kota Surakarta, Kabupaten Karanganyar dan Sukoharjo) - Rachman Djamal; Wiwin Widiastuti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
The potential for community activities in the city waste management problems is part of the research of integrated waste management in the city of Surakarta , Karanganyar and Sukoharjo in 2011 served to complement the advice and input in tackling the problems of waste management in Central Java. The method used in this study a descriptive analysis by primary data (indept interview, discution focused group), secondary data (waste regulation, waste statistics and the results of studies). The results showed that waste management in three locations have been referring to the existing regulation, but still a lack of adequate funding, facilities, personnel executing the operation and management of an integrated waste management system in accordance with the standard operating procedure . Most people at the neighborhood level, residents, village has conducted programs 3 R (reduse, reuse, and recycle) as a potential community activities in order to reduce the waste management problems of the city. Therefore it is necessary to increase the participation of the community through increased implementation of outreach programs - education and training - pilot project using existing institutions such PKK (empowering the livelihoods of families), Karang Taruna and others in order to expand the scope implementation of the program 3 R. Increasing the intensity of community participation in the city 's waste management needs to be linked to integrated waste management programs through government collaboration, the University/R&D institutions and private institution.